Qana’ah as a Qur’anic Spiritual Disposition: Its Conceptual Relevance to Mental-Health Self-Diagnosis in Digital Contexts - Teguh Perdana; Achyar Zein (Journal of Indonesian Islamic Studies, 2026)
The growing circulation of mental-health content on social media has expanded access to psychological vocabulary while also increasing the possibility that individuals interpret ordinary distress as a clinical disorder without professional assessment. This article examines the conceptual relevance of qana’ah to mental-health self-diagnosis and specifies the safeguards required for a responsible Islamic response. The study uses a qualitative conceptual design that combines thematic Qur’anic exegesis with an integrative literature review. Six passages—Q. 9:59, 16:97, 20:131, 57:23, 65:3, and 49:6—were analyzed through al-Tabari, Ibn Kathir, Hamka, and M. Quraish Shihab, while peer-reviewed studies on qana’ah, mental-health literacy, misinformation, self-diagnosis, and help-seeking were coded comparatively. The analysis identifies qana’ah as an active disposition comprising gratitude, sufficiency, proportionate desire, continued effort, and reliance on God. Conceptually, these qualities may support emotional regulation and create an interpretive pause before distress is converted into a diagnostic identity. Qana’ah alone, however, does not establish diagnostic accuracy. Its protective relevance becomes more coherent when joined to tabayyun as information verification, mental-health literacy as symptom-context differentiation, and professional consultation as a clinical safeguard. The article therefore proposes qana’ah as a complementary spiritual framework rather than a substitute for psychological or psychiatric care. Because the model is conceptual, its proposed pathways require empirical testing across diverse Muslim populations and digital environments.